Carbon-Fiber-Reinforced PEEK Intramedullary Nails Defining the Niche - Georges F. Vles; Maximillian H. Brodermann; Mark A. Roussot; James Youngman (Case Reports in Orthopedics)
Background. Carbon-fiber-reinforced Polyetheretherketone (CFR-PEEK) nails are gaining interest as they have biomechanical properties potentially capable of overcoming disadvantages of conventional metal nails. Case Summary. Three cases are illustrated which required superior mechanical toughness, compatibility with radiotherapy, and postoperative advanced imaging. Conclusion. CFR-PEEK nails seem to have a niche role in distinct groups of patients.